Consumer perception of product carbon footprint labelling : A concept proposal - Szabo, Jonathan (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2021)
The aim of this paper is to determine how a carbon footprint label for grocery products can be designed to facilitate a sustainable consumption behaviour. Therefore, a mixed-method approach was used consisting out of a review of relevant literature and an explorative quantitative survey with n=158 participants. It was found that consumers generally have a positive attitude towards carbon labelling, but they lack understanding of the term, its underlying concepts and the emissions caused by grocery products. In regard to the design criteria of a carbon label, labels with a coloured scale are preferred most by consumers. Also, the mechanisms of consumer behaviour imply that not all parts of the behaviour are visible and controllable for individuals themselves. The concluding concept proposal summarises important criteria of a carbon labelling system that has the goal to educate consumers and facilitate a lower carbon consumption behaviour, such as a simple visual design, the use of a colour scale, a design enabling a comparison, the provision of a link to further information, the public enforcement of the system and overall uniformity.
A concept proposal
Keywords: 333.7 Natürliche Ressourcen, Energie und Umwelt